WhatsApp Messenger application among business students in Malaysia – an exploration - Noor Azuan Hashim,; Nor Liza Abdullah,; Rosmah Mat Isa,; Hawati Janor, (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia, 2015)
WhatsApp Messenger, one of the social media applications on smart phone is gaining popularity as a mode of social interaction recently. Many people, particularly part-time university students,have used this application, not only for daily communication but also for discussion on their academic tasks. Therefore, high level of usage of this application is expected amongst part-time university student in Malaysia. However, little is understood from empirical viewpoint about the intensity of WhatsApp messenger usages and its impact on the academic performance of students in the university. This study seeks to investigate the perceived impact of WhatsApp messengeron the academic performance of university students in Malaysia. A survey and face-to-face interviews were carried-out which involved 86 part-time students in the survey and 15 students in the interviews. The findings indicated that WhatsApphas enhanced effective flow of information and idea sharing among students. Despite making communication easier and faster, WhatsApp has also negative impact on the performance of students. The studyrevealed that: WhatsApphas taken much of students study time and concentration because they are being bothered by the incoming messages. This resulted in procrastination due to inabilities to manage time in balancing online activities, lack of concentration during lectures and academic discussion, distracts students from completing their assignments and affecting student ability in spelling and grammatical construction of sentences on assignments. In addition, some issues on the WhatsApp application were also discussed.